Cotranslational insertion of selenocysteine into formate dehydrogenase from Escherichia coli directed by a UGA codon. - Zinoni, F (1987)
The structural gene (fdhF) for the 80-kDa selenopolypeptide of formate dehydrogenase (formate:benzyl viologen oxidoreductase, EC 1.2.--.--) from Escherichia coli contains an in-frame UGA codon at amino acid position 140 that is translated. Translation of gene fusions between N-terminal parts of fdhF with lacZ depends on the availability of selenium in the medium when the hybrid gene contains the UGA codon; it is independent of the presence of selenium when an fdhF portion upstream of the UGA position is fused to lacZ. Transcription does not require the presence of selenium in either case. By localized mutagenesis, the UGA codon was converted into serine (UCA) and cysteine (UGC and UGU) codons. Each mutation relieved the selenium dependency of fdhF mRNA translation. Selenium incorporation was completely abolished in the case of the UCA insertion and was reduced to about 10% when the UGA was replaced by a cysteine codon. Insertion of UCA yielded an inactive fdhF gene product, while insertion of UGC and UGU resulted in polypeptides with lowered activities as components in the system formerly known as formate hydrogenlyase. Altogether the results indicate that the UGA codon at position 140 directs the cotranslational insertion of selenocysteine into the fdhF polypeptide chain.